Meal intake in an adult Moroccan population: determinants and implications for weight status - Imane Barakat; Sanaa El-Jamal; Hamid Chamlal; Houda Elfane; Halima Daif; Mohammed Elayach; Rekia Belahsen (National Institute of Public Health - National Institute of Hygiene, 2023)
Background: In recent decades, the Moroccan population has changed its dietary practices, particularly those related to meal-taking. It is about irregular meal schedules, reduced frequency and shorter time of meal-taking times, as well as a decrease in family meal-taking. All these factors are likely to influence its nutritional status. Objective: The aim is to study meal-taking practices, their determinants and their implications on weight status. In this study, meal-taking practices are defined by the regularity of the schedule, the frequency and the duration of the meals as well as the family commensality. Material and Methods: This work data are part of a study conducted among 507 households in the region of Rabat-Salé-Kenitra in Morocco, with a validated conceptual and methodological framework. The questionnaire was completed with one member of each household and the body mass index (BMI) was determined by an impedance meter. Results: The main results indicate that the majority of the surveyed population was aged 35 years (59%), female (52%), urban (70%), with a BMI ≥25 kg/m2 (51%), took usually three meals a day (89%), spent less than 90 minutes a day in meals and snacks (60%), had irregular meal schedule (69%), and usually eat at least two meals or snacks a day with family (49%). The univariate analysis showed that urban area was a factor favoring variations of meal times, the male sex was a factor favoring three meals a day, the level of higher education was a factor penalizing the daily duration of meals, and that marital status "married" was a factor favoring family commensality. In addition, variable meal times were revealed as a factor contributing to overweight/obesity, and meal times ≥90 min were revealed as a protective factor of overweight/ obesity. Conclusion. The study identified factors associated with meal times, frequency and duration. The results obtained will serve as a basis for the development of educational actions for a change in behavior conducive to health.